PENGARUH PELATIHAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT WALUYA HIRUP BAGJA - Akep Aura; Imam Muhtadin (Taksasila Edukasi Insani, 2025)
Employee performance (Y) is a determining factor in company productivity, particularly in the consulting services sector. This study analyzes the effect of job training (X1) and competency (X2) on employee performance at PT Waluya Hirup Bagja, a management and digital consulting firm in Kemang District, Bogor Regency. The research method used a quantitative approach with purposive sampling of 60 employees. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed: (1) Job training had a positive and significant effect on performance (β=0.281; p0.05), (2) employee competency had a stronger effect (β=0.392; p0.05). Simultaneously, X1 and X2 contributed 52.3% to the variation in performance (R²=0.523). These findings reinforce the importance of needs-based training and regular competency assessment in consulting services firms. Practical implications: PT Waluya Hirup Bagja can optimize its HR development program to increase business competitiveness. Keywords : Job training, competency, employee performance, management consulting, linear regression.